Functions of Aurora kinase C in meiosis and cancer - Quartuccio, Suzanne M.; Schindler, Karen (Frontiers in Cell and Developmental Biology, 2015)
The mammalian genome encodes three Aurora kinase protein family members: A, B, and C. While Aurora kinase A (AURKA) and B (AURKB) are found in cells throughout the body, significant protein levels of Aurora kinase C (AURKC) are limited to cells that undergo meiosis (sperm and oocyte). Despite its discovery nearly 15 years ago, we know little about the function of AURKC compared to that of the other 2 Aurora kinases. This lack of understanding can be attributed to the high sequence homology between AURKB and AURKC preventing the use of standard approaches to understand non-overlapping and meiosis I (MI)-specific functions of the two kinases. Recent evidence has revealed distinct functions of AURKC in meiosis and may aid in our understanding of why chromosome segregation during MI often goes awry in oocytes. Many cancers aberrantly express AURKC, but because we do not fully understand AURKC function in its normal cellular context, it is difficult to predict the biological significance of this expression on the disease. Here, we consolidate and update what is known about AURKC signaling in meiotic cells to better understand why it has oncogenic potential.